2017
DOI: 10.1208/s12249-017-0845-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surfactants on Mechanical, Thermal, and Photostability of a Monoclonal Antibody

Abstract: The purpose of this work was to evaluate the effect of commonly used surfactants (at 0.01% w/v concentration) on mechanical, thermal, and photostability of a monoclonal antibody (MAb1) of IgG1 sub-class and to evaluate the minimum concentration of surfactant (Polysorbate 80) required in protecting MAb1 from mechanical stress. Surfactants evaluated were non-ionic surfactants, Polysorbate 80, Polysorbate 20, Pluronic F-68 (polyoxyethylene-polyoxypropylene block polymer), Brij 35 (polyoxyethylene lauryl ether), T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…4 Surface active molecules, such as polysorbates (PSs), are common excipients in drug product formulations to increase colloidal stability and minimize adsorption of proteins to interfaces. 5,6 PSs are nonionic surfactants containing mainly sorbitan polyoxyethylene (POE) fatty acid esters. The protective role of PS in protein formulations has been thoroughly investigated, 7 and 2 main mechanisms have been elucidated: (1) PS acting as a chaperone for aggregation-prone hydrophobic sites on the protein surfaces (promoting the folded structure) 8,9 and (2) PS competing with proteins at interfaces (reducing interface exposure).…”
Section: Introductionmentioning
confidence: 99%
“…4 Surface active molecules, such as polysorbates (PSs), are common excipients in drug product formulations to increase colloidal stability and minimize adsorption of proteins to interfaces. 5,6 PSs are nonionic surfactants containing mainly sorbitan polyoxyethylene (POE) fatty acid esters. The protective role of PS in protein formulations has been thoroughly investigated, 7 and 2 main mechanisms have been elucidated: (1) PS acting as a chaperone for aggregation-prone hydrophobic sites on the protein surfaces (promoting the folded structure) 8,9 and (2) PS competing with proteins at interfaces (reducing interface exposure).…”
Section: Introductionmentioning
confidence: 99%
“…A rational formulation design chosen by optimizing solution conditions and the addition of excipients can significantly increase AAV stability and thus shelf-life. The usefulness of excipients on recombinant proteins has been extensively reported, 97,104,105,107,119,121,123,148 and excipients can in a similar way play a major role in the safety and efficacy of viral vectors. However, there is a lack of a rational, methodologically structured and systematic method of excipient selection.…”
Section: Rational Formulation Design Using Excipientsmentioning
confidence: 99%
“…Surfactants are generally added in mAbs formulations to reduce the exposure of hydrophobic regions and so decreasing proteinprotein interactions and interface-induced aggregation, also prevented by competition for adsorption sites. 129,130 Frequently used nonionic surfactants in mAb drug formulation are polysorbate 20 and polysorbate 80, 17,83 with poloxamers being a potential alternative. 131 Indeed, polysorbate 80 seems to be one of the most protecting surfactant against mechanical stresseinduced aggregation when compared to some other nonionic and anionic surfactants at the same concentration, 130 and also seems to be less perturbing toward mAb higher structure stability when compared to polysorbate 20.…”
Section: Excipientsmentioning
confidence: 99%
“…132 This protection also depends on the protein to surfactant ratio. 29,93,130 In addition, surfactants have been shown to act as chemical chaperones, increasing rates of protein refolding and thus reducing aggregation. 46,47 For example, Gerhardt et al 133 reported that addition of polysorbate 20 to a solution containing various concentrations of a humanized IgG 1 antibody reduced particle formation during incubation or agitation with siliconized glass syringes, but noted a lack of correlation between the critical micelle concentration of the surfactant and its protective effect against aggregation.…”
Section: Excipientsmentioning
confidence: 99%